2015
DOI: 10.1021/ef502210z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Functionalized Poly(glycidyl methacrylate)-Based Particles for the Selective Removal of Nitrogen Compounds from Light Gas Oil: Effect of Linker Length

Abstract: In this work, four poly­(glycidyl methacrylate-co-ethylene glycol methacrylate) [PGMA-co-EDGMA] functionalized particles were synthesized and characterized, and tested in gas oil adsorption. Particles consisted of identical polymer support (PGMA-co-EDGMA, henceforth referred to as PGMA) and π-acceptor moiety (2,4,5,7-tetranitroflorenone, TENF), while the linkers (linear diamines) were varied from a two- (diaminoethane, DAE (2)), a three- (diaminopropane, DAP­(3)) to a four-carbon (diaminobutane, DAB­(4)) conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
6
14
0
Order By: Relevance
“…To ensure that the removal of nitrogen compounds was solely due to the polymer alone, blank tests were performed. Although nitrogen adsorption was higher in the batch scale, Chitanda et al also experienced a 6% (from 19% to 13%) decrease in total nitrogen adsorption after just one regeneration of the polymer. Similarly, in this study, there was a 4% (from 10.5% to 6.5%) decrease in nitrogen adsorption after the first regeneration.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…To ensure that the removal of nitrogen compounds was solely due to the polymer alone, blank tests were performed. Although nitrogen adsorption was higher in the batch scale, Chitanda et al also experienced a 6% (from 19% to 13%) decrease in total nitrogen adsorption after just one regeneration of the polymer. Similarly, in this study, there was a 4% (from 10.5% to 6.5%) decrease in nitrogen adsorption after the first regeneration.…”
Section: Resultssupporting
confidence: 53%
“…Based on the following results, it can be concluded that bulk polymer mass had an effect on polymer activity with regard to nitrogen adsorption. Higher nitrogen adsorption was experienced on the batch scale as compared with the pilot scale. However, for sulfur adsorptions, there was no difference between the batch and pilot scale because both had no change in sulfur removal, indicating that bulk polymer mass had no effect on sulfur removal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we aimed to develop a simple and effective strategy for PVC‐based medical films to enhance their antifouling properties and long‐term stability. It is well known that glycidyl methacrylate (GMA) with epoxy pendants is able to react with functional groups, such as amino, hydroxyl, or carboxyl groups, on the surface of a substrate . Therefore, poly(3‐sulfopropyl methacrylate–methacrylatoethyl trimethyl ammonium chloride–glycidyl methacrylate) (PSTG) copolymers were synthesized by free‐radical polymerization.…”
Section: Introductionmentioning
confidence: 99%